(3GbJUGOjGJ GdfbhO hGdeGd (B:s (3GdfXQjI hGdeDSSGJ GdfbOjI,HhQUI GdChQGb GdeGdjI aj eUQ,JWhQ GdfXGe GdeUQaj GdeUQj (B/s - (3TgGH, eLOj eMehOs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2000)
(3GdfbhO,GdfbhO aj GbJUGO GdeHGOdI,CTcGd GdfbhO,bjeI GdfbhO,JbOjQ bjeI GdfbhO,BKGQ GdJZjjQ aj bjeI GdfbhO hXGgQI GdJVNe,GdfXe GdfbOjI,GdfXGe GdfbOj GdeUQj,GdShb GdfbOj,Shb QCS GdeGd,Shb GdeGd aj eUQ,JWhQ GdfXGe GdeUQaj aj WQjbI GdGfJGL GdQCSeGdj,fTCI hJWhQ GdLgGR GdeUQaj aj eUQ,gjcd hCgejI GdLgGR GdeUQaj GdeUQjs
(3HHdjhZQGajG(B:(3U(B.281-283s
Keywords: (3GdEbJUGOs; (3GdfbhOs